An aluminum alloy composite material having an axial-radial double gradient ceramic network reinforcement and a method of manufacturing the same
Patent Information
- Application Number
- CN202610831904.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-23
AI Technical Summary
中国专利CN117802423B采用静电纺丝技术制备Al2O3/SiC复合陶瓷纤维膜,粉碎后混入铝合金,但纤维膜粉碎后变成短纤维碎片,失去了膜的连续性优势,实质仍为短纤维增强
1. 本发明中将铝合金基体放入三维网络预制体的目的是构建双连续相互贯穿的结构,使陶瓷网络作为增强骨架承担载荷,在保持铝合金轻量化优势的同时大幅提升整体刚度、强度和抗疲劳性能;一是显著提升刚度,陶瓷网络弹性模量远高于铝合金,连续网络可实现线面接触的应力传递,使复合材料整体刚度大幅提高,同等刚度下可显著减薄壁厚;二是阻断裂纹扩展,三维连续网络构成立体屏障,使裂纹扩展时被强制偏转或桥接,疲劳寿命较传统颗粒增强材料大幅提升;三是实现外刚内韧的梯度匹配,通过双梯度设计使表面陶瓷含量高、孔径细密以提供刚度和耐磨性,芯部陶瓷含量低以保持断裂韧性;四是提供优异的耐磨性与尺寸稳定性,表面陶瓷网络使耐磨性显著提高,低热膨胀系数有效约束铝合金热变形;
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum alloy materials technology, specifically to an aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network and its preparation method. Background Technology
[0002] Aluminum-based composite materials, due to their lightweight and high strength, have broad application prospects in aerospace, rail transportation, military equipment, and industrial robots. As industrial robots develop towards lightweight, high precision, and high dynamic response, higher requirements are placed on the specific stiffness, fatigue resistance, dimensional stability, and wear resistance of structural materials. Miniature six-axis industrial robots, as core equipment in precision assembly and flexible manufacturing scenarios, require their external structural components, such as the base, upper arm, forearm, and joint housing, to withstand complex alternating loads, impact loads, and abrasive wear during service, while maintaining high repeatability and positioning accuracy over long-term operation. While traditional wrought aluminum alloys such as 6061 and 7075 possess good machinability and toughness, their elastic modulus is only about 70 GPa, resulting in insufficient specific stiffness to meet the lightweight requirements of high-rigidity structural components. Furthermore, their wear resistance is poor, and they are prone to precision degradation after long-term use. To improve the mechanical properties of aluminum alloys, scholars both domestically and internationally have conducted extensive research. Particle-reinforced aluminum-based composite materials, by introducing ceramic particles such as SiC, Al2O3, and TiB2 into the aluminum matrix, can significantly improve the strength and elastic modulus of the material. For example, patent CN113403511A discloses a high-strength, tough, weldable, in-situ nano-reinforced rare-earth aluminum alloy. This alloy achieves phase-separated reinforcement within the grains and at grain boundaries by introducing in-situ nano-ceramic particles and rare-earth precipitates, resulting in a tensile strength of up to 480 MPa and an elongation of 16.3%. However, in this technology, the ceramic particles are discretely distributed, leading to discontinuous load transfer paths, limited reinforcement efficiency, and a tendency for particles to agglomerate at grain boundaries, causing localized stress concentration and reduced toughness. Patent CN117626065A uses a hybrid reinforcement of nano-ceramic particles and micron-sized silicon carbide fibers, increasing the tensile strength to 548 MPa. However, the fibers are randomly distributed and lack orientation, and the nanoparticles are prone to agglomeration, making further performance breakthroughs difficult. Three-dimensional continuous network reinforced aluminum matrix composites have become a research hotspot in recent years. Their interconnected reinforcing phases and continuous load transfer paths significantly improve the overall stiffness and fatigue resistance of the composite material. Chinese patent CN117802423B uses electrospinning technology to prepare Al2O3 / SiC composite ceramic fiber membranes, which are then pulverized and mixed into aluminum alloys. However, the pulverized fiber membrane becomes short fiber fragments, losing its continuity advantage and essentially remaining a short fiber reinforcement. Existing network reinforcement technologies mostly employ uniformly distributed single network structures, making it difficult to achieve spatial gradient matching of material properties. However, the service characteristics of robot external structural components—where the surface must withstand contact stress and wear, and the core must maintain toughness—necessitate gradient design. Furthermore, existing technologies use limited strengthening methods for the aluminum alloy matrix, often employing a single nanophase or a single aged precipitate. The dispersion and interfacial bonding strength of the nano-reinforcing phase still need improvement, and the poor interfacial wettability between the molten aluminum and the ceramic network easily leads to interfacial debonding, severely affecting the overall performance of the composite material. Summary of the Invention
[0003] The technical problem to be solved: The purpose of this invention is to propose an aluminum alloy composite material with axial-radial dual-gradient ceramic network reinforcement and its preparation method. Through the dual-gradient structure design of axial composition gradient and radial pore size gradient, combined with dual nano-dispersion reinforced aluminum alloy matrix and multi-level stepped aging heat treatment, the stiffness of the composite material is doubled and the strength and toughness are synergistically improved.
[0004] Technical solution: An aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network, the composite material being composed of an aluminum alloy matrix and a three-dimensional continuous dual-gradient ceramic-carbon composite network reinforcement phase; The composition of the aluminum alloy matrix by weight percentage is: Zn 5.5-6.5%, Mg 2.0-2.6%, Cu 1.2-1.8%, Sc 0.15-0.25%, Zr 0.08-0.15%, Nb 0.05-0.1%, with the balance being Al and unavoidable impurities; The matrix contains 0.1-0.3% nano-TiB2 particles; The ceramic-carbon composite network reinforcement phase is a composite ceramic skeleton of Al2O3, SiC and TiC with a mass ratio of (4-6):3:1, and 0.03-0.05wt% short carbon fiber filaments are added. The inner wall of the network is adsorbed with a composite layer of graphene and carbon nanotubes. The reinforcement phase has a dual gradient structure with axial composition gradient and radial pore size gradient.
[0005] The above-mentioned method for preparing aluminum alloy composite material reinforced with axial-radial dual-gradient ceramic network includes the following steps: S1. Preparation of aluminum alloy matrix: Weigh the aluminum alloy matrix raw materials according to the formula, add nano TiB2 particles modified with silane coupling agent, perform ultrasonic treatment and electromagnetic stirring during the melting process, and anneal after casting; S2. Fabrication of dual-gradient ceramic network preforms: S21. A sponge template with a radial pore size gradient is immersed in a graphene-carbon nanotube dispersion for surface modification, and then completely immersed in an Al2O3 / SiC / TiC composite ceramic slurry with short carbon fiber filaments added. The slurry is then fully filled with sponge pores through vacuum infiltration. S22. The saturated impregnated sponge template is vertically lifted to form an axial ceramic load gradient, wherein the top ceramic load is lower than the bottom ceramic load. S23. The pulled template is dried and sintered to obtain a dual-gradient three-dimensional ceramic-carbon composite network preform with both radial pore size gradient and axial composition gradient. S3. Pressure infiltration composite: The preform obtained in step S23 is surface treated and preheated, while the aluminum alloy prepared in step S1 is remelted. Then the molten aluminum alloy is poured onto the preheated preform, pressure is applied and ultrasonic assistance is used for infiltration, and after cooling, a composite blank is obtained. S4. Densification and Stepped Aging: The composite billet is densified by hot isostatic pressing, followed by solution treatment and multi-stage aging to obtain the aluminum alloy composite material.
[0006] Preferably, the sponge template with radial pore size gradient in step S21 is an open-cell polyurethane sponge with a central region pore size of 500-600 μm and an edge region pore size of 200-300 μm; the mass ratio of graphene to carbon nanotubes in the dispersion is (1-3):1; the solid content of the Al2O3 / SiC / TiC composite ceramic slurry is 20-40 vol%; and the amount of chopped carbon fiber added is 0.03-0.05 wt% of the composite ceramic slurry.
[0007] Preferably, the frequency of the ultrasonic treatment in step S1 is 20-30kHz, and the ultrasonic power is 1000-1500W; the rotation speed of the electromagnetic stirring is 250-500r / min; and the temperature of the homogenization annealing is 460-480℃, and the time is 12-24h.
[0008] Preferably, the vertical lifting speed in step S22 is 2-5 mm / s, and the resulting axial gradient is: the top ceramic load is 15-20 vol%, and the bottom ceramic load is 35-40 vol%.
[0009] Preferably, the sintering process in step S23 is as follows: under an inert atmosphere, the temperature is increased to 400-600℃ at 5℃ / min and held for 2 hours, and then increased to 1350-1450℃ at 5℃ / min and held for 3 hours.
[0010] Preferably, the surface treatment in step S3 includes plasma spraying of an Al-Si transition layer and attachment of V2O5; the Si content in the Al-Si transition layer is 8-10%, and the V2O5 concentration is 0.1-0.2%; the preheating temperature is 580-620℃, the aluminum alloy remelting temperature is 720-740℃, the applied pressure is 60-80MPa, and the holding time is 15-25s.
[0011] Preferably, the hot isostatic pressing process parameters in step S4 are: 480-500℃, 120-150MPa, 2-3h; solution treatment is 470℃×1-2h followed by water quenching; multi-stage aging consists of three stages: 120℃×24h, 300℃×1-2h, and 180℃×4h.
[0012] The above-mentioned aluminum alloy composite material reinforced with axial-radial dual-gradient ceramic network is used in the external structural components of mini six-axis industrial robots.
[0013] Beneficial effects: The aluminum alloy composite material of the present invention has the following advantages: 1. The purpose of placing the aluminum alloy matrix into the three-dimensional network preform in this invention is to construct a double continuous and interpenetrating structure, allowing the ceramic network to act as a reinforcing skeleton to bear the load. This significantly improves the overall stiffness, strength, and fatigue resistance while maintaining the lightweight advantage of aluminum alloy. Firstly, it significantly enhances stiffness. The elastic modulus of the ceramic network is much higher than that of the aluminum alloy, and the continuous network enables stress transfer through line-to-surface contact, greatly increasing the overall stiffness of the composite material. At the same stiffness, the wall thickness can be significantly reduced. Secondly, it inhibits crack propagation. The three-dimensional continuous network forms a three-dimensional barrier, forcibly deflecting or bridging cracks during propagation, resulting in a significantly longer fatigue life compared to traditional particle-reinforced materials. Thirdly, it achieves a gradient match between external stiffness and internal toughness. The dual-gradient design ensures high surface ceramic content and fine pore size to provide stiffness and wear resistance, while the core ceramic content is low to maintain fracture toughness. Fourthly, it provides excellent wear resistance and dimensional stability. The surface ceramic network significantly improves wear resistance, and the low coefficient of thermal expansion effectively constrains the thermal deformation of the aluminum alloy. 2. The multi-level nano-reinforcement system formed by the multi-level aging process in step S4 of this invention improves the yield strength, tensile strength, and elongation of the aluminum alloy matrix. Simultaneously, the axial-radial dual-gradient ceramic-carbon composite network prepared in step S2 serves as a three-dimensional continuous reinforcing skeleton, increasing the overall elastic modulus and specific stiffness of the composite material. Under the same load conditions, the structural component wall thickness is reduced, achieving significant weight reduction. 3. In this invention, the synergistic effect of the plasma-sprayed Al-Si transition layer and the V2O5-induced in-situ generated Al3V interfacial reaction layer, combined with the covalent bridging of graphene-carbon nanotubes on the inner wall of the ceramic network and the toughening effect of short-cut carbon fiber filaments, enhances the interfacial shear strength between the aluminum matrix and the ceramic network, solving the technical problem of easy peeling at the interface of ceramic-reinforced aluminum alloys. After hot isostatic pressing densification, the fatigue life of the composite material under cyclic loading is improved compared with traditional particle-reinforced aluminum alloys. Detailed Implementation
[0014] The present invention will be further described below with reference to embodiments. These embodiments are illustrative of the present invention, but the present invention is not limited to these embodiments: An aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network: S1. Preparation of aluminum alloy matrix: Ultrasonic and electromagnetic stirring are used for synergistic melting to make nano-TiB2 particles uniformly dispersed in the matrix and avoid agglomeration; annealing treatment promotes the precipitation of Al3(Nb,Zr) phase, forming a nano-scale dispersed strengthening phase, which provides nucleation sites for subsequent age strengthening; S21. Sponge template modification: Graphene-carbon nanotubes are adsorbed onto the inner wall of the sponge, forming a carbon-based interface layer after high-temperature sintering, which improves the wettability of ceramics and molten aluminum. At the same time, the high modulus of carbon materials is used to further enhance the overall stiffness of the composite material. S22. Vertical lifting creates an axial gradient: Gravity causes the slurry to flow downwards, with more loss at the top and less at the bottom, naturally forming an axial gradient in the ceramic load that decreases from bottom to top, resulting in differentiated properties at different locations of the material; S23. Sintering: At high temperature, solid-phase diffusion and necking occur between ceramic particles to form a three-dimensional continuous network framework; at the same time, carbon materials and ceramics undergo interfacial reactions to form covalent bonds, which enhances the stability of the network structure. S3. Pressure infiltration composite: The Al-Si transition layer improves the wettability of aluminum liquid and ceramic; V2O5 reacts in situ with aluminum liquid at high temperature to generate Al3V reaction layer. This reaction layer and Al-Si layer work together to form a dual interface structure, eliminating interface debonding defects and greatly improving the interface bonding strength.
[0015] S4. Densification and Stepped Aging: Hot isostatic pressing eliminates residual porosity from infiltration, achieving full densification of the material. In stepped aging: the η-type main strengthening phase precipitates in the low-temperature stage; the Al3(Sc,Zr) core-shell particles are stabilized and grain boundaries are pinned in the medium-temperature stage; the TiB2 and matrix interface is optimized and the distribution of precipitated phases is adjusted in the high-temperature stage, ultimately forming a multi-level nano-synergistic strengthening system.
[0016] Example 1 A method for preparing aluminum alloy composites reinforced with axial-radial dual-gradient ceramic networks includes the following steps: S1. Preparation of aluminum alloy matrix: 0.2% nano-TiB2 particles modified with KH560 were added after Zn 5%, Mg 2.0%, Cu 1.5%, Sc 0.15%, Zr 0.1%, Nb 0.1%, and Al 91.15%. The mixture was ultrasonically treated at 20kHz for 30min during the melting process and electromagnetically stirred at 300r / min. After casting, it was annealed at 460℃ for 16h. S2. Fabrication of dual-gradient ceramic network preforms: S21. Select an open-cell polyurethane sponge with a pore size of 500 μm, radially compress it into a conical mold with an inner diameter gradually increasing from 40 mm to 50 mm, heat-treat it at 150℃ for 60 min, cool and demold it to obtain a gradient sponge with a core pore size of approximately 500 μm and an edge pore size of approximately 200 μm. Immerse it in a graphene-carbon nanotube dispersion for surface modification, wherein the mass ratio of graphene to carbon nanotubes in the dispersion is 2:1 and the concentration is 0.1 wt%; then completely immerse it in Al2O3 with a solid content of 35 vol% and a mass ratio of 6:3:1. 3 / SiC / TiC composite ceramic slurry with 0.05wt% chopped carbon fiber was infiltrated under a vacuum of -0.09MPa for 5 minutes to fill the pores.
[0017] S22. The saturated impregnated sponge template is vertically lifted at a speed of 5 mm / s to form an axial ceramic load gradient of 20 vol% at the top and 35 vol% at the bottom. S23. After drying the pulled template, degrease it by heating it to 500℃ at 5℃ / min and holding it for 2 hours under an inert atmosphere, and then sinter it at 1350℃ at 5℃ / min and holding it for 3 hours to obtain a dual-gradient three-dimensional ceramic-carbon composite network preform with both radial pore size gradient and axial composition gradient. S3. Pressure infiltration composite: The preform obtained in step S23 is plasma-sprayed with an Al-Si (Si content 10%) transition layer and 0.1% V2O5 is attached, and then preheated to 600℃; at the same time, the aluminum alloy prepared in step S1 is remelted to 720℃, poured onto the preheated preform, pressure of 80MPa is applied and held for 20s, and ultrasonic infiltration is assisted by 15kHz, 300W. After cooling, a composite blank is obtained. S4. Densification and Stepped Aging: The composite billet is densified by hot isostatic pressing at 500℃ and 120MPa for 2 hours; then it is solution treated at 470℃ and water quenched for 2 hours; finally, multi-stage aging is carried out: 120℃×24h, 300℃×1.5h, and 180℃×4h to obtain the aluminum alloy composite material.
[0018] Example 2
[0019] A method for preparing aluminum alloy composites reinforced with axial-radial dual-gradient ceramic networks includes the following steps: S1. Preparation of aluminum alloy matrix: 0.3% nano-TiB2 particles modified with KH560 were added after Zn 6%, Mg 2.5%, Cu 1.2%, Sc 0.25%, Zr 0.15%, Nb 0.1%, and Al 89.8%. The alloy was ultrasonically treated at 30kHz for 30min during the melting process and electromagnetically stirred at 300r / min. After casting, it was annealed at 480℃ for 16h. S2. Fabrication of dual-gradient ceramic network preforms: S21. A sponge template with a radial pore size gradient was selected, consisting of an open-cell polyurethane sponge with a central pore size of 500 μm and an edge pore size of 200 μm. This sponge was then immersed in a graphene-carbon nanotube dispersion for surface modification. The dispersion contained graphene to carbon nanotubes in a 1:1 mass ratio and a concentration of 0.5 wt%. Finally, it was completely immersed in Al₂O₃ with a solid content of 30 vol% and a mass ratio of 4:3:1. 3 / SiC / TiC composite ceramic slurry with 0.03wt% chopped carbon fiber was infiltrated under a vacuum of -0.09MPa for 3 minutes to fill the pores.
[0020] S22. The saturated impregnated sponge template is vertically lifted at a speed of 2 mm / s to form an axial ceramic load gradient of 15 vol% at the top and 40 vol% at the bottom. S23. After drying the pulled template, degrease it by heating it to 400℃ at 5℃ / min and holding it for 2h under an inert atmosphere, and then sinter it at 1450℃ at 5℃ / min and holding it for 2h to obtain a dual-gradient three-dimensional ceramic-carbon composite network preform with both radial pore size gradient and axial composition gradient. S3. Pressure infiltration composite: The preform obtained in step S23 is plasma-sprayed with an Al-Si (8% Si) transition layer and 0.2% V2O5 is attached, and then preheated to 580°C; at the same time, the aluminum alloy prepared in step S1 is remelted to 740°C, poured onto the preheated preform, subjected to a pressure of 60MPa for 25s, and then infiltrated with ultrasonic assistance at 20kHz and 250W. After cooling, a composite blank is obtained. S4. Densification and Stepped Aging: The composite billet is densified by hot isostatic pressing at 480℃ and 150MPa for 3 hours; then it is solution treated at 480℃ and water quenched for 1 hour; finally, multi-stage aging is carried out: 120℃×20h, 300℃×2h, and 180℃×3h to obtain the aluminum alloy composite material.
[0021] Example 3
[0022] A method for preparing aluminum alloy composites reinforced with axial-radial dual-gradient ceramic networks includes the following steps: S1. Preparation of aluminum alloy matrix: 0.15% nano-TiB2 particles modified with KH560 were added after the following composition: Zn 5.5%, Mg 2.2%, Cu 1.8%, Sc 0.20%, Zr 0.12%, Nb 0.08%, Al 90.1%. The mixture was ultrasonically treated at 25kHz for 30min during the melting process and electromagnetically stirred at 300r / min. After casting, it was annealed at 470℃ for 12h. S2. Fabrication of dual-gradient ceramic network preforms: S21. A sponge template with a radial pore size gradient was selected, consisting of an open-cell polyurethane sponge with a central pore size of 550 μm and an edge pore size of 220 μm. This sponge was then immersed in a graphene-carbon nanotube dispersion for surface modification. The dispersion contained graphene to carbon nanotubes in a mass ratio of 3:1 and a concentration of 0.8 wt%. Finally, it was completely immersed in Al₂O₃ with a solid content of 40 vol% and a mass ratio of 5:3:1. 3 / SiC / TiC composite ceramic slurry with 0.04wt% chopped carbon fiber was infiltrated under a vacuum of -0.09MPa for 4 minutes to fill the pores.
[0023] S22. The saturated impregnated sponge template is vertically lifted at a speed of 3 mm / s to form an axial ceramic load gradient of 18 vol% at the top and 38 vol% at the bottom. S23. After drying the pulled template, it is degreased by heating to 450℃ at 5℃ / min and holding for 1.5h under an inert atmosphere, and then sintered at 1400℃ at 5℃ / min for 2.5h to obtain a dual-gradient three-dimensional ceramic-carbon composite network preform with both radial pore size gradient and axial composition gradient. S3. Pressure infiltration composite: The preform obtained in step S23 is plasma-sprayed with an Al-Si (Si content 9%) transition layer and 0.15% V2O5 is attached, and then preheated to 610°C; at the same time, the aluminum alloy prepared in step S1 is remelted to 730°C, poured onto the preheated preform, subjected to a pressure of 70MPa for 18s, and then subjected to ultrasonic infiltration at 18kHz and 280W. After cooling, a composite blank is obtained. S4. Densification and Stepped Aging: The composite billet is densified by hot isostatic pressing at 490℃ and 130MPa for 2.5h; then it is solution treated at 475℃ and water quenched for 1.5h; finally, multi-stage aging is carried out: 120℃×22h, 300℃×1.5h, and 180℃×4h to obtain the aluminum alloy composite material.
[0024] Example 4
[0025] A method for preparing aluminum alloy composites reinforced with axial-radial dual-gradient ceramic networks includes the following steps: S1. Preparation of aluminum alloy matrix: 0.25% nano-TiB2 particles modified with KH560 were added after Zn 6.5%, Mg 2.6%, Cu 1.6%, Sc 0.22%, Zr 0.08%, Nb 0.09%, and Al 89.11%. The mixture was ultrasonically treated at 20kHz for 30min during the melting process and electromagnetically stirred at 300r / min. After casting, it was annealed at 465℃ for 16h. S2. Fabrication of dual-gradient ceramic network preforms: S21. A sponge template with a radial pore size gradient was selected, consisting of an open-cell polyurethane sponge with a central pore size of 580 μm and an edge pore size of 240 μm. This sponge was then immersed in a graphene-carbon nanotube dispersion for surface modification. The dispersion contained graphene to carbon nanotubes in a mass ratio of 2:1 and a concentration of 0.3 wt%. Finally, it was completely immersed in Al₂O₃ with a solid content of 33 vol% and a mass ratio of 6:3:1. 3 / SiC / TiC composite ceramic slurry with 0.05wt% chopped carbon fiber was permeated under a vacuum of -0.085MPa for 5 minutes to fill the pores.
[0026] S22. The saturated impregnated sponge template is vertically lifted at a speed of 4 mm / s to form an axial ceramic load gradient of 20 vol% at the top and 35 vol% at the bottom. S23. After drying the pulled template, degrease it by heating it to 550℃ at 5℃ / min and holding it for 2 hours under an inert atmosphere, and then sinter it at 1380℃ at 5℃ / min and holding it for 3 hours to obtain a dual-gradient three-dimensional ceramic-carbon composite network preform with both radial pore size gradient and axial composition gradient. S3. Pressure infiltration composite: The preform obtained in step S23 is plasma-sprayed with an Al-Si (Si content 10%) transition layer and 0.12% V2O5 is attached, and then preheated to 620°C; at the same time, the aluminum alloy prepared in step S1 is remelted to 725°C, poured onto the preheated preform, subjected to a pressure of 75MPa for 22s, and then infiltrated with ultrasonic assistance at 15kHz and 350W. After cooling, a composite blank is obtained. S4. Densification and Stepped Aging: The composite billet is densified by hot isostatic pressing at 495℃ and 140MPa for 2 hours; then it is solution treated at 470℃ and water quenched for 2 hours; finally, multi-stage aging is carried out: 120℃×24h, 300℃×1.5h, and 180℃×4h to obtain the aluminum alloy composite material.
[0027] Example 5
[0028] A method for preparing aluminum alloy composites reinforced with axial-radial dual-gradient ceramic networks includes the following steps: S1. Preparation of aluminum alloy matrix: 0.1% nano-TiB2 particles modified with KH560 were added after the following composition: Zn 5.8%, Mg 2.4%, Cu 1.4%, Sc 0.18%, Zr 0.13%, Nb 0.07%, Al 90.02%. The mixture was ultrasonically treated at 28kHz for 30min during the melting process and electromagnetically stirred at 300r / min. After casting, it was annealed at 460℃ for 16h. S2. Fabrication of dual-gradient ceramic network preforms: S21. A sponge template with a radial pore size gradient was selected, consisting of an open-cell polyurethane sponge with a central pore size of 600 μm and an edge pore size of 260 μm. This sponge was then immersed in a graphene-carbon nanotube dispersion for surface modification. The dispersion contained graphene to carbon nanotubes at a mass ratio of 1.5:1 and a concentration of 1.0 wt%. Then, it was completely immersed in Al₂O₃ with a solid content of 38 vol% and a mass ratio of 4.5:3:1. 3 / SiC / TiC composite ceramic slurry with 0.035wt% chopped carbon fiber was permeated under -0.09MPa vacuum for 2 minutes to fill the pores.
[0029] S22. The saturated impregnated sponge template is vertically lifted at a speed of 2.5 mm / s to form an axial ceramic load gradient with a top ceramic load of 16 vol% and a bottom ceramic load of 37 vol%. S23. After drying the pulled template, it is degreased by heating to 600℃ at 5℃ / min and holding for 1h under an inert atmosphere, and then sintered at 1420℃ at 5℃ / min and holding for 2h to obtain a dual-gradient three-dimensional ceramic-carbon composite network preform with both radial pore size gradient and axial composition gradient. S3. Pressure infiltration composite: The preform obtained in step S23 is plasma-sprayed with an Al-Si (Si content 8.5%) transition layer and 0.18% V2O5 is attached, and then preheated to 590°C; at the same time, the aluminum alloy prepared in step S1 is remelted to 735°C, poured onto the preheated preform, subjected to a pressure of 65MPa for 15s, and then subjected to ultrasonic infiltration at 25kHz and 200W. After cooling, a composite blank is obtained. S4. Densification and Stepped Aging: The composite billet is densified by hot isostatic pressing at 485℃ and 125MPa for 2 hours; then it is solution treated at 465℃ and water quenched for 2 hours; finally, multi-stage aging is carried out: 120℃×24h, 300℃×1.5h, and 180℃×4h to obtain the aluminum alloy composite material.
[0030] Comparative Example 1 The main difference between Comparative Example 1 and Example 1 is that no ceramic network preform is prepared; only the aluminum alloy substrate is subjected to the same S1 and S4 treatments. That is, the aluminum alloy substrate prepared by step S1 is directly used to obtain the material after hot isostatic pressing and stepped aging treatment in step S4. The rest is the same as in Example 1.
[0031] Comparative Example 2 The main difference between Comparative Example 2 and Example 1 is that the sponge template adopts a uniform pore size design and does not undergo radial pore size gradient treatment. A 500μm open-cell polyurethane sponge is selected, and without conical mold compression heat treatment, the uniform pore size sponge is directly used for subsequent impregnation and lifting; simultaneously, the vertical lifting process is carried out at a uniform speed to avoid forming an axial ceramic load gradient, resulting in a uniform distribution of the ceramic network. The rest is the same as in Example 1.
[0032] Comparative Example 3 The main difference between Comparative Example 3 and Example 1 is that: no graphene-carbon nanotube composite layer and chopped carbon fiber filaments are added in step S21; the sponge template is not modified with graphene-carbon nanotube dispersion, and no chopped carbon fiber filaments are added to the ceramic slurry. Comparative Example 4 The main difference between Comparative Example 4 and Example 1 is that KH560 modified nano-TiB2 particles are not added in step S1, while the rest is the same as in Example 1.
[0033] Comparative Example 5 The main difference between Comparative Example 5 and Example 1 is that the interface transition layer treatment is not performed in step S3. That is, the preform obtained in step S23 is not plasma-sprayed with an Al-Si transition layer, nor is V2O5 attached; it is directly preheated and then pressure impregnated. The rest is the same as in Example 1.
[0034] Comparative Example 6 The main difference between Comparative Example 6 and Example 1 is that single-stage aging is used in step S4, without multi-stage aging; that is, after hot isostatic pressing and solution treatment, only a single-stage aging treatment of 120℃×24h is performed, without the aging steps of 300℃×1.5h and 180℃×4h. The rest is the same as in Example 1.
[0035] Comparative Example 7 The main difference between Comparative Example 7 and Example 1 is that commercially available 6061 aluminum alloy is used instead of the aluminum alloy matrix of the present invention, and no ceramic network preform is prepared. That is, the 6061 aluminum alloy is directly subjected to T6 heat treatment (solution treatment at 530°C for 1 hour, water quenching, and artificial aging at 175°C for 8 hours), and the rest is different from Example 1.
[0036] Performance testing: 1. Density and relative density test According to the GB / T 3850-2015 standard, the Archimedes displacement method was used to measure the sample density. Each sample was measured 5 times and the average value was taken. The relative density was calculated based on the theoretical density.
[0037] 2. Elastic modulus test The elastic modulus of the sample was measured using the dynamic resonance method according to GB / T 22315-2008 standard; the sample size was 50mm×10mm×3mm, the test temperature was 25±2℃, and the relative humidity was 50±5%.
[0038] 3. Tensile property test Tensile testing at room temperature was conducted using an electronic universal testing machine according to GB / T 228.1-2010 standard. The tensile rate was 2 mm / min, the gauge length was 25 mm, and five parallel samples were tested for each example and comparative example, with the average value taken. The test parameters included yield strength, tensile strength, and elongation after fracture.
[0039] 4. Interface shear strength test The interfacial shear strength between the aluminum matrix and the ceramic network was tested using the micro-shear method. The sample size was 10 mm × 5 mm × 5 mm, the loading rate was 0.5 mm / min, and 10 different interfacial regions were tested for each sample, and the average value was taken.
[0040] 5. Fatigue performance testing Stress-controlled high-cycle fatigue testing was conducted using a high-frequency fatigue testing machine in accordance with GB / T 3075-2008 standard. The stress ratio R=0.1, the frequency was 100Hz, a sinusoidal wave was used, and the stress amplitude was set at 200MPa, with the test being conducted until the specimen fractured or the number of cycles reached 1×10⁻⁶. 7 The next step is the termination condition; fatigue life is recorded.
[0041] 6. Thermal expansion coefficient test According to GB / T 4339-2008 standard, the average linear thermal expansion coefficient of the samples in the temperature range of 30-200℃ was measured using a thermomechanical analyzer. The heating rate was 5℃ / min, and each sample was measured 3 times and the average value was taken.
[0042] 7. Surface hardness test The surface hardness of the samples was measured using a Vickers hardness tester according to GB / T 4340.1-2009 standard. The applied load was 1 kg, and the holding time was 15 s. Ten different locations were measured for each sample, and the average value was taken.
[0043] Table 1 Example 1 2.68 99.5 96 482 552 10.2 138 <![CDATA[>1×10 7 ]]> 15.8 162 Example 2 2.69 99.4 97 495 565 9.5 142 <![CDATA[>1×10 7 ]]> 15.5 168 Example 3 2.67 99.6 94 470 540 11.0 135 <![CDATA[>1×10 7 ]]> 16.2 158 Example 4 2.70 99.3 98 488 558 9.8 140 <![CDATA[>1×10 7 ]]> 15.3 165 Example 5 2.68 99.5 95 465 535 10.8 130 <![CDATA[>1×10 7 ]]> 16.0 155 Comparative Example 1 2.71 99.2 72 315 385 14.2 — <![CDATA[2.3×10 6 ]]> 23.2 118 Comparative Example 2 2.69 99.0 83 425 495 6.2 112 <![CDATA[4.2×10 6 ]]> 19.5 142 Comparative Example 3 2.68 99.1 88 438 505 8.5 105 <![CDATA[5.8×10 6 ]]> 18.2 148 Comparative Example 4 2.68 99.3 94 385 445 12.5 132 <![CDATA[7.6×10 6 ]]> 16.5 150 Comparative Example 5 2.69 98.5 90 445 515 9.2 62 <![CDATA[3.5×10 6 ]]> 17.5 145 Comparative Example 6 2.69 99.2 93 405 475 7.5 130 <![CDATA[2.8×10 6 ]]> 16.8 148 Comparative Example 7 2.70 — 69 260 310 12.0 — <![CDATA[1.5×10 6 ]]> 23.5 95 As shown in Table 1, the relative densities of Examples 1-5 all reached over 99.3%, indicating that the pressure infiltration combined with hot isostatic pressing process used in this invention can effectively eliminate residual porosity inside the composite material, achieving near-full densification. Comparative Example 5, due to the lack of an interface transition layer treatment, had micropores at the interface, resulting in a slightly lower relative density of 98.5%. The relative densities of Comparative Examples 1, 2, 3, 4, and 6 were comparable to those of the Examples. Comparative Example 7, a conventional 6061 aluminum alloy, had a relative density close to the theoretical value. The densities of Examples 1-5 were 2.67-2.70 g / cm³, only slightly higher than those of conventional aluminum alloys, indicating that ceramic network reinforcement maintains the lightweight advantage of aluminum alloys while achieving performance improvement. The elastic modulus of Examples 1-5 was 94-98 GPa, an increase of approximately 36-45% compared to the conventional 6061 aluminum alloy of Comparative Example 7. Comparative Example 1, without a ceramic network, had an elastic modulus of only 72 GPa, demonstrating the decisive role of the ceramic network in improving stiffness. Comparative Example 2, using a uniform ceramic network, had an elastic modulus of 83 GPa, lower than that of the dual-gradient design, indicating that the dual-gradient structure can... The load can be transferred more effectively; Comparative Example 3, without the addition of carbon nanotubes and carbon fibers, has an elastic modulus of 88 GPa, which is lower than that of the Example, demonstrating the further enhancement of stiffness by carbon materials; Comparative Examples 4 and 6 have elastic moduli close to those of the Example, indicating that the influence of TiB2 nanoparticles and multi-stage aging on the elastic modulus is relatively small, and the elastic modulus is mainly contributed by the ceramic network; The yield strength of Examples 1-5 is 465-495 MPa, and the tensile strength is 535-565 MPa, which are about 79-90% and 73-82% higher than that of the 6061 aluminum alloy in Comparative Example 7, respectively. Example 2 exhibited the highest strength, which is related to its high Zn and Mg content and high TiB2 addition. Comparative Example 1, containing only an aluminum alloy matrix, had a yield strength of 315 MPa. Comparative Example 2, using a uniform ceramic network, had a yield strength of 425 MPa, approximately 12% lower than Example 1. The dual-gradient structure allowed the load to be transferred from the outside to the inside, reducing stress concentration and thus improving strength. Comparative Example 3, without the addition of carbon materials, had a yield strength of 438 MPa, a decrease of approximately 9%, demonstrating the effect of carbon materials in improving the continuity of the reinforcing phase. Comparative Example 4, without the addition of TiB2 particles, had a yield strength of 385 MPa, a decrease of approximately 20%. The results demonstrate the crucial role of dual-nano TiB2 in strengthening the matrix. Comparative Example 5, lacking an interface transition layer, exhibits a yield strength of 445 MPa, a decrease of approximately 8%, indicating that weakened interfacial bonding leads to reduced load transfer efficiency. Comparative Example 6, employing single-stage aging, achieves a yield strength of 405 MPa, a decrease of approximately 16%. Comparative Example 7, made of 6061 aluminum alloy, exhibits the lowest strength. In terms of plasticity, Examples 1-5 show elongation rates of 9.5-11.0%, which, while lower than the pure matrix alloy of Comparative Example 1, are superior to Comparative Examples 2 and 6. This demonstrates that the dual-gradient design achieves a gradient match between external stiffness and internal toughness, maintaining good plasticity while achieving high strength.
[0044] The interfacial shear strength of Examples 1-5 was 130-142 MPa, while the untreated interface of Comparative Example 5 only reached 62 MPa. Example 2 achieved the highest 142 MPa, which is related to its optimized infiltration parameters; Comparative Example 3, without the addition of carbon materials, had an interfacial shear strength of 105 MPa, demonstrating the improving effect of graphene-carbon nanotubes on interfacial bonding; the interfacial shear strengths of Comparative Examples 4 and 6 were comparable to those of the Examples, indicating that TiB2 and the aging process had little impact on interfacial bonding; good interfacial bonding is the foundation for the excellent mechanical properties of composite materials, and the dual interfacial control technology utilizes the synergistic effect of the Al-Si transition layer and the Al3V in-situ reaction layer; under a stress amplitude of 200 MPa, the fatigue life of Examples 1-5 all exceeded 1 × 10⁻⁶. 7 No fracture occurred. The fatigue life of Comparative Example 1 was 2.3 × 10⁻⁶. 6 This demonstrates the inhibitory effect of ceramic networks on fatigue crack propagation. The fatigue lives of Comparative Example 2 and Comparative Example 3 were 4.2 × 10⁻⁶. 6 The sum is 5.8 × 10⁻⁶. 6 This demonstrates, in a sub-example, the improvement in fatigue performance caused by the dual-gradient structure and carbon materials.
[0045] The coefficients of thermal expansion for Examples 1-5 are 15.3-16.2 × 10⁻⁵. -6 / K, which is approximately 31-35% lower than the conventional aluminum alloy in Comparative Example 7. Comparative Example 1, without the ceramic network, has a coefficient of thermal expansion of 23.2 × 10⁻⁶. -6 / K, proving the effective constraint of the ceramic network on the hot deformation of the aluminum alloy; Comparative Example 2 uses a uniform network with a thermal expansion coefficient of 19.5×10. -6 / K, higher than the example, demonstrates the improvement in dimensional stability brought about by the dual-gradient structure; Comparative Example 3, without the addition of carbon material, has a coefficient of thermal expansion of 18.2 × 10⁻⁶. -6 The surface hardness of Examples 1-5 is slightly higher than that of the Examples 1-5, demonstrating the contribution of carbon materials to reducing the coefficient of thermal expansion. A lower coefficient of thermal expansion means that the thermal deformation of the structural components is smaller after the robot has been running for a long time and generating heat, which is beneficial to maintaining high repeatability and positioning accuracy. The surface hardness of Examples 1-5 is 155-168 HV, which is 63-77% higher than that of the 6061 aluminum alloy in Comparative Example 7. The surface hardness of Example 2 reaches 168 HV, which is related to the high ceramic loading. The surface hardness of Comparative Examples 2 and 3 is lower, demonstrating the contribution of the dual-gradient structure and carbon materials to the surface properties. The hardness of Comparative Example 4 is 150 HV, which is slightly lower, but the hardness of Comparative Example 5 is 145 HV, demonstrating that the interface bonding has a certain influence on the hardness. The higher surface hardness makes the material have better wear resistance under contact friction conditions.
[0046] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. An aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network, characterized in that: The composite material consists of an aluminum alloy matrix and a three-dimensional continuous dual-gradient ceramic-carbon composite network reinforcement phase. The composition of the aluminum alloy matrix by weight percentage is: Zn 5.5-6.5%, Mg 2.0-2.6%, Cu 1.2-1.8%, Sc 0.15-0.25%, Zr 0.08-0.15%, Nb 0.05-0.1%, with the balance being Al and unavoidable impurities; The matrix contains 0.1-0.3% nano-TiB2 particles; The ceramic-carbon composite network reinforcement phase is a composite ceramic skeleton of Al2O3, SiC and TiC with a mass ratio of (4-6):3:1, and 0.03-0.05wt% short carbon fiber filaments are added. The inner wall of the network is adsorbed with a composite layer of graphene and carbon nanotubes. The reinforcement phase has a dual gradient structure with axial composition gradient and radial pore size gradient.
2. The method for preparing the aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network according to claim 1, characterized in that... This includes the following steps: S1. Preparation of aluminum alloy matrix: Weigh the aluminum alloy matrix raw materials according to the formula, add nano TiB2 particles modified with silane coupling agent, perform ultrasonic treatment and electromagnetic stirring during the melting process, and anneal after casting; S2. Fabrication of dual-gradient ceramic network preforms: S21. A sponge template with a radial pore size gradient is immersed in a graphene-carbon nanotube dispersion for surface modification, and then completely immersed in an Al2O3 / SiC / TiC composite ceramic slurry with short carbon fiber filaments added. The slurry is then fully filled with sponge pores through vacuum infiltration. S22. The saturated impregnated sponge template is vertically lifted to form an axial ceramic load gradient, wherein the top ceramic load is lower than the bottom ceramic load. S23. The pulled template is dried and sintered to obtain a dual-gradient three-dimensional ceramic-carbon composite network preform with both radial pore size gradient and axial composition gradient. S3. Pressure infiltration composite: The preform obtained in step S23 is surface treated and preheated, while the aluminum alloy prepared in step S1 is remelted. Then the molten aluminum alloy is poured onto the preheated preform, pressure is applied and ultrasonic assistance is used for infiltration, and after cooling, a composite blank is obtained. S4. Densification and Stepped Aging: The composite billet is densified by hot isostatic pressing, followed by solution treatment and multi-stage aging to obtain the aluminum alloy composite material.
3. The method for preparing the aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network according to claim 2, characterized in that: The preparation steps of the radial pore size gradient sponge template in step S21 are as follows: Select an open-cell polyurethane sponge with a basic pore size of 300-500μm, compress it radially and put it into a cylindrical mold with a tapered inner diameter, then heat treat it at 130-150°C and keep it at that temperature for 45-90 minutes to allow the sponge structure to creep and solidify, and finally cool and demold to obtain a radial pore size gradient sponge template with a central region pore size of 500-600μm and an edge region pore size of 200-300μm.
4. The method for preparing the aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network according to claim 2, characterized in that: The ultrasonic treatment in step S1 is performed at a frequency of 20-30 kHz, and the homogenization annealing is performed at a temperature of 460-480 °C for 12-24 h.
5. The method for preparing the aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network according to claim 2, characterized in that: The vertical lifting speed described in step S22 is 2-5 mm / s, and the resulting axial gradient is: 15-20 vol% for the top ceramic load and 35-40 vol% for the bottom ceramic load.
6. The method for preparing the aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network according to claim 2, characterized in that: The sintering process described in step S23 is as follows: under the protection of an inert atmosphere, the temperature is increased to 400-600℃ at 5℃ / min and held for 2 hours, and then the temperature is increased to 1350-1450℃ at 5℃ / min and held for 3 hours.
7. The method for preparing the aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network according to claim 2, characterized in that: The surface treatment in step S3 includes plasma spraying of an Al-Si transition layer and attachment of V2O5; the preheating temperature is 580-620℃, the aluminum alloy remelting temperature is 720-740℃, the applied pressure is 60-80MPa, and the holding time is 15-25s.
8. The method for preparing the aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network according to claim 2, characterized in that: The hot isostatic pressing process parameters in step S4 are: 480-500℃, 120-150MPa, 2-3h; solution treatment is 470℃×1-2h followed by water quenching; multi-stage aging consists of three stages: 120℃×24h, 300℃×1-2h, and 180℃×4h.
9. The application of the aluminum alloy composite material reinforced with an axial-radial dual-gradient ceramic network according to claim 1 in the external structural components of a mini six-axis industrial robot.
Citation Information
Patent Citations
High-strength and high-elongation aluminum alloy material and preparation method thereof
CN117626065A
A composite ceramic fiber reinforced aluminum alloy material and its preparation method
CN117802423B